A Novel Case of Reccurrent Hemarthrosis in a Patient with Undiagnosed Hemophilia - Ramadhita, Nova; Kurniawan, Yudhi (Jurnal Biologi Tropis, 2025)
Hemophilia is an inherited X-linked recessive bleeding disorder characterized by deficiency of coagulation factors and commonly presents with hemarthrosis that may lead to permanent joint damage if diagnosis is delayed. This report aims to describe a case of recurrent hemarthrosis that led to the diagnosis of previously unrecognized hemophilia B. We report a 3-year-old boy with progressive swelling and pain of the left knee following minor trauma and surgical intervention, with a history of easy bruising and prolonged bleeding after circumcision. Laboratory evaluation showed prolonged activated partial thromboplastin time with normal prothrombin time and platelet count, and coagulation factor assay revealed factor IX activity of 1.2%, consistent with moderate hemophilia B. Recurrent hemarthrosis in this patient was the key clinical manifestation that prompted further diagnostic evaluation. This case highlights that recurrent or persistent joint bleeding in children, especially in the absence of a clear family history, should raise strong suspicion of hemophilia. Early recognition through careful bleeding history, coagulation screening, and specific factor assays is essential to prevent long-term musculoskeletal complications and unnecessary surgical procedures.